2023
DOI: 10.3390/ijms241512519
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Biomarkers of Neuro-Glial Injury in Human Status Epilepticus: A Systematic Review

Giada Giovannini,
Stefano Meletti

Abstract: As per the latest ILAE definition, status epilepticus (SE) may lead to long-term irreversible consequences, such as neuronal death, neuronal injury, and alterations in neuronal networks. Consequently, there is growing interest in identifying biomarkers that can demonstrate and quantify the extent of neuronal and glial injury. Despite numerous studies conducted on animal models of status epilepticus, which clearly indicate seizure-induced neuronal and glial injury, as well as signs of atrophy and gliosis, evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Comparison of six serum biomarkers (S100B, NSE, GFAP, UCH-L1, NFL, and t-tau) within 24 h of TBI found that GFAP had the highest discrimination for predicting CT abnormalities with a 99% likelihood of better discrimination. However, in mild TBI, the discrimination increased from 0.84 to 0.89; although this was statistically significant, it is only a small increase, with unknown clinical significance [49].…”
Section: Monitoringmentioning
confidence: 79%
“…Comparison of six serum biomarkers (S100B, NSE, GFAP, UCH-L1, NFL, and t-tau) within 24 h of TBI found that GFAP had the highest discrimination for predicting CT abnormalities with a 99% likelihood of better discrimination. However, in mild TBI, the discrimination increased from 0.84 to 0.89; although this was statistically significant, it is only a small increase, with unknown clinical significance [49].…”
Section: Monitoringmentioning
confidence: 79%
“…Some shortcomings need to be acknowledged, however. Clinical variables associated with the risk of seizure occurrence after SE, such as the time to first‐line treatment initiation, 21 peri‐ictal MRI abnormalities, 30 and fluid biomarkers of neurodegeneration and neuroinflammation, 31 were not available for all subjects and were not included. One major flaw was that it was not possible to explore in depth the potential impact of the treatment with ASMs, thereby limiting the generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%